Monochlorotetrazinyl Reactive Dyes: Synthesis and Characterization - Tutak, Mustafa; Disli, Ali; Alicilar, Ahmet (Asian Journal of Chemistry, 2010)
In present studies, the synthesis and characterization of monochlorotetrazinyl reactive dyes are reported. Triaminoguanidine monohydrochloride was prepared by reacting guanidine hydrochloride with hydrazine monohydrate and then, converted to 3,6-bis(3,5-dimethylpyrazol-1-yl)-1,2- dihydro-1,2,4,5-tetrazine by adding 2,4-pentanedione. 3,6-Dihydrazino- 1,2,4,5-tetrazine was obtained by the reaction between 3,6-bis(3,5- dimethylpyrazol-1-yl)-1,2-dihydro-1,2,4,5-tetrazine and hydrazine monohydrate. 3,6-Dichloro-1,2,4,5-tetrazine was formed by passing chlorine through 3,6-dihydrazino-1,2,4,5-tetrazine. The structures of products were confirmed by melting points, HPLC, FT-IR, 13C or 1H NMR and mass spectral data. The chromophore groups of three different dyestuffs known (Reactive blue 4, orange 1 and red 2) were prepared and characterizated by 1H NMR. By reacting trichlorotriazinyl and dichlorotetrazinyl groups with them, dichlorotriazinyl and monochlorotetrazinyl dyes were obtained and their dyeing efficiencies on cotton were tried to be determined in subsequent studies.